2017
DOI: 10.1007/s11136-017-1575-8
|View full text |Cite
|
Sign up to set email alerts
|

Online support groups for head and neck cancer and health-related quality of life

Abstract: PurposeTo investigate the association between using online support groups (OSGs) and health-related quality of life (HRQoL), and the psychosocial factors that may influence this association among individuals with head and neck (H&N) cancer.MethodA sample of 199 persons with H&N cancer using four OSGs completed an online questionnaire using six pre-validated measures for social network, self-efficacy, anxiety and depression, adjustment, empowerment and quality of life. In addition, socio-demographic as well as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 49 publications
0
19
0
1
Order By: Relevance
“…Studies have previously been conducted that looked at the effect of ISG in cancer patients. These studies found an overall positive effect of an ISG on psychosocial outcomes [55][56][57]. There are, however, substantial differences between the ISG used in these studies and the one used in w-SPIINA.…”
Section: Discussionmentioning
confidence: 90%
“…Studies have previously been conducted that looked at the effect of ISG in cancer patients. These studies found an overall positive effect of an ISG on psychosocial outcomes [55][56][57]. There are, however, substantial differences between the ISG used in these studies and the one used in w-SPIINA.…”
Section: Discussionmentioning
confidence: 90%
“…Indeed, a recent study with HNC patients and carers (Al Gtewi, Owens, & Baker, 2017) found evidence to suggest that the use of online support groups may be associated with better quality of life and lower levels of depression and anxiety. HNC patients may feel unable to talk about appearance with health care professionals because it is seen as a 'luxury' or frivolous issue.…”
Section: Discussionmentioning
confidence: 99%
“…Receiving peer support from people who have experienced similar changes maybe particularly valuable in building a sense of community that can facilitate building of selfesteem, and health care professionals might look to more readily sign post patients to organizations such as Changing Faces (see www.changingfaces.org.uk). Indeed, a recent study with HNC patients and carers (Al Gtewi, Owens, & Baker, 2017) found evidence to suggest that the use of online support groups may be associated with better quality of life and lower levels of depression and anxiety.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies found that peer-to-peer online platforms can be sources of information and support. Peers provide these sources themselves by helping other users or to emotionally support each other [7][8][9][10][11][12]. Online empowering processes can facilitate empowering outcomes outside the online environment such as being better informed, feeling more confident with the physician, and improved acceptance of the disease [1].…”
Section: Introductionmentioning
confidence: 99%